1979
DOI: 10.1021/ja00498a043
|View full text |Cite
|
Sign up to set email alerts
|

Infrared photochemistry of a volatile uranium compound with 10-.mu. absorption

Abstract: oxides.13 This approach can also explain the conversion14 of Z allylic derivatives into olefins with predominant E configuration by a displacement with LiCuMe2. The nature of the leaving group should be decisive in determining which mechanism will be operative: ion pairs should be easily formed from common allylic esters compared with the corresponding lithium carbamates in the presence of copper reagents acting as Lewis acids.15This hypothesis is now under investigation, while evaluation of the scope and limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…The use of volatile U(OMe)6 for uranium isotope separation/enrichment via IR laser-induced multiphoton excitations has received much attention. [77][78][79][80][81][82] The key molecular requirements for any efficient laser-induced isotope separation process employing polyatomic molecules include (i) volatility, (ii) the existence of an infrared-active normal vibrational mode that exhibits a nonzero isotope shift and absorbs in a spectral region corresponding to the output of an efficient laser system, (iii) the absence of interfering ligand absorptions, (iv) the ready synthesis of large quantities of the target molecule, (v) the facile separation and recycling of enriched and depleted material, and (vi) the absence of undesirable photochemical side reactions.…”
Section: Molecular Structuresmentioning
confidence: 99%
“…The use of volatile U(OMe)6 for uranium isotope separation/enrichment via IR laser-induced multiphoton excitations has received much attention. [77][78][79][80][81][82] The key molecular requirements for any efficient laser-induced isotope separation process employing polyatomic molecules include (i) volatility, (ii) the existence of an infrared-active normal vibrational mode that exhibits a nonzero isotope shift and absorbs in a spectral region corresponding to the output of an efficient laser system, (iii) the absence of interfering ligand absorptions, (iv) the ready synthesis of large quantities of the target molecule, (v) the facile separation and recycling of enriched and depleted material, and (vi) the absence of undesirable photochemical side reactions.…”
Section: Molecular Structuresmentioning
confidence: 99%
“…Much research in this area is classified, but there are numerous public reports as well. Weitz et al 165 synthesized U(OCH& for convenient IRMPD from a C02 laser and observed enrichment in 235U. In general, LIS schemes for uranium based on IRMPD have not shown high selectivities, due to small isotope shifts and spectral congestion.…”
Section: )mentioning
confidence: 99%